Answer: First option. x-intercept is -5; y-intercept is -7/4
Solution:
1) To find the x-intercept we replace y by 0, and solve for x:
-(7/5)x-4y=7
-(7/5)x-4(0)=7
-(7/5)x-0=7
-(7/5)x=7
Multiplying both sides of the equation by -(5/7)
-( 5/7)[-(7/5)]x=-(5/7)(7)
x=-(5*7)/7
x=-35/7
x=-5
The x-intercept is -5
2) To find the y-intercept we replace x by 0, and solve for y:
-(7/5)x-4y=7
-(7/5)(0)-4y=7
-0-4y=7
-4y=7
Dividing both sides of the equation by -4:
-4y/(-4)=7/(-4)
y=-(7/4)
The y-intercept is -(7/4)